The development of the chondrocranium of Ascaphus Truei Stejneger with special reference to the relations of the palatoquadrate to the neurocranium - Van Eeden, J. A (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1950.